Modeling the Ultrasonic Atomization Process of Milk and Powder Production Using Spray Drying Method - Ali Heydari; Masoud Goharimanesh; Mohammadreza Gharib; Ali Koochi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2023)
Introduction The beneficial use of ultrasonic systems has been proven in many applications. Among them, ultrasonic atomization is widely used in various industries, including food and coating industries. Ultrasonic vibrations of liquids can produce fine droplets called atomized fluid. During the fluid atomization process, droplet size and distribution can be precisely controlled so that the droplets become very small and high-level particle distribution is achieved which can be easily evaporated. This method is widely used in various industries, including food industry (for the production of driedpowder products) and coating industry. The key factor that affects droplet size is the frequency and amplitude of the ultrasonic vibrations and the properties of the fluid, including the fluid viscosity and surface tension. Materials and Methods Based on a review of literature, it is clear that the modeling of the ultrasonic method for spray dryers and the production of milk powder has not been done so far. In the present work, first, the research background is reviewed and then, using the relationships provided for the ultrasonic atomization of different fluids in the reviewed articles, the effect of ultrasonic vibrations on the atomization and evaporation of milk as a food and the powder production was studied using spray drying process. Then the effects of various oscillation parameters such as frequency, amplitude and also the temperature of the fluid, which affects its viscosity, density and surface tension, on the rate of atomization of the fluid was investigated. In the present work, we first examine the fluid whose range of properties is true in relations. One of the most widely used liquids in the food industry is milk. By examining the viscosity, surface tension and density of the milk and obtaining the dimensionless numbers We, In and Oh, it is determined that the provided relations can also be used for milk. After calculating the diameter of the evaporated particles of milk due to ultrasonic vibrations as well as the evaporation rate, the independent variables of the research can be changed. First, in the constant physical properties of a fluid, we change the frequency and amplitude of ultrasonic oscillations and studied their effect on the produced particle diameter and evaporation rate. In the next step, with the constant frequency and amplitude of ultrasonic oscillations, the effect of changes in fluid properties (temperature change) on the produced particle diameter and evaporation rate was investigated. In the next stepthe effect of frequency and amplitude of ultrasonic fluctuations as well as changes in fluid properties (temperature change) on the powder diameter produced and the time required for the drying process was investigated. The analysis of all data obtained from the above steps was performed using Mathlab software. Results and Discussion The main and summary results obtained from the present study are as follows: